2012
DOI: 10.1007/s10753-012-9455-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Platelet Activating Factor, Platelet Activating Factor Acetylhydrolase Levels and Risk of Coronary Heart Disease or Blood Stasis Syndrome of Coronary Heart Disease in Chinese: A Case Control Study

Abstract: The purpose of the study was to explore the association between plasma platelet activating factor (PAF) and platelet activating factor acetylhydrolase (PAF-AH) levels and risk of coronary heart disease (CHD) or blood stasis syndrome (BSS) of CHD. Questionnaire, routine clinical assays and plasma levels of PAF, PAF-AH and inflammatory factors hs-CRP and IL-6 were investigated or measured for 120 controls and 150 CHD patients (66 non-BSS and 84 BSS). Plasma PAF levels were higher in CHD patients [49.7 (34.8-73.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Consistently, a recent study reported elevated plasma levels of both PAF and Lp-PLA 2 mass in a cohort of coronary heart disease (CHD) patients compared with a control group ( 54 ). Increased Lp-PLA 2 mass in this setting may represent in vivo evidence for PAF-and/or OxPL-mediated effects on Lp-PLA 2 expression.…”
Section: Biochemical and Structural Propertiessupporting
confidence: 56%
“…Consistently, a recent study reported elevated plasma levels of both PAF and Lp-PLA 2 mass in a cohort of coronary heart disease (CHD) patients compared with a control group ( 54 ). Increased Lp-PLA 2 mass in this setting may represent in vivo evidence for PAF-and/or OxPL-mediated effects on Lp-PLA 2 expression.…”
Section: Biochemical and Structural Propertiessupporting
confidence: 56%
“…PAF affects the gene expression of Lp-PLA2), as shown in a recent study involving 150 patients with CHD and 120 controls that found a strong positive relationship between elevated plasma PAF or Lp-PLA2 levels and the risk of CHD. This study also provided evidence that there was a strong correlation between plasma PAF and Lp-PLA2 levels, and between plasma PAF and Lp-PLA2 and inflammatory factors IL-6 and hs-CRP levels (Zheng et al, 2012).…”
Section: The Pafr Inhibition By Darapladib and Rilapladib Hypothesissupporting
confidence: 60%
“…Amid a sea of various other oxidation products produced during LDL oxidation, butanoyl and butenoyl species ( Table 1 ) account for the bulk of the PAF activity, and these PAF mimetics were identifi ed to be up to 1/10th as potent as PAF ( 11 ). In a case control study, mean plasma PAF levels of 23.8 pg/ml were reported in healthy subjects while CVD patients had elevated PAF levels of 49.7 pg/ml ( 39 ). Studies by Ninio and her coworkers detected the presence of PAF preferentially in intermediate LDL during LDL oxidation, where it reached up to 8.6 ± 5.7 pmol/mg in 3 h of oxidation ( 40 ).…”
Section: Risk Factor or A Risk Marker?mentioning
confidence: 99%